A Garden of Quanta: Essays in Honor of Hiroshi Ezawa - A. Tonomura (World Scientific, 2003)
This collection of reviews and essays about the wide-ranging developments in the areas of quantum physics has mostly been written at the graduate level, but some are accessible to advanced undergraduates. They should serve as good introductions for beginning graduate students in quantum physics who are looking for directions. Aspects of mathematical physics, quantum field theories and statistical physics are emphasized.